SPIO-conjugated, doxorubicin-loaded microbubbles for concurrent MRI and focused-ultrasound enhanced brain-tumor drug delivery - Fan, Ching-Hsiang; Ting, Chien-Yu; Lin, Han-Jung; Wang, Chung-Hsin; Liu, Hao-Li; Yen, Tzu-Chen; Yeh, Chih-Kuang (Biomaterials, 2013)
The blood–brain barrier (BBB) can be temporarily and locally opened by focused ultrasound (FUS) in the presence of circulating microbubbles (MBs). Currently, contrast-enhanced magnetic resonance imaging (CE-MRI) is used to monitor contrast agent leakage to verify BBB-opening and infer drug deposition. However, despite being administered concurrently, MBs, therapeutic agent, and contrast agent have distinct pharmacodynamic behaviors, thus complicating the quantification and optimization of BBB-opening and drug delivery. Here we propose multifunctional MBs loaded with therapeutic agent (doxorubicin; DOX) and conjugated with superparamagnetic iron oxide (SPIO) nanoparticles. These DOX-SPIO-MBs were designed to concurrently open the BBB and perform drug delivery upon FUS exposure, act as dual MRI and ultrasound contrast agent, and allow magnetic targeting (MT) to achieve enhanced drug delivery. We performed burst-tone FUS after injection of DOX-SPIO-MBs, followed by MT with an external magnet attached to the scalp in a rat glioma model. Animals were monitored by T2-weighted MRI and susceptibility weighted imaging and the concentration of SPIO particles was determined by spin–spin relaxivity. We found that DOX-SPIO-MBs were stable and provided significant superparamagnetic/acoustic properties for imaging. BBB-opening and drug delivery were achieved concurrently during the FUS exposure. In addition, MT increased local SPIO deposition in tumor regions by 22.4%. Our findings suggest that DOX-SPIO-MBs with FUS could be an excellent theranostic tool for future image-guided drug delivery to brain tumors.